IMPROVING STUDENTSâ VOCABULARY MASTERY BY USING SCRABBLE AT THE SIXTH GRADE STUDENTS AT SD NEGERI 007 BANGUN PURBA - Prayitno, Puji; Sukma, Dian; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research used Classroom Action Research (CAR) to improved studentsâ vocabulary mastery at sixth grade students of SD Negeri 007 Bangun Purba. There were 32 students, they were 16 males and 16 females. In this research used two cycles. In this research, the researcher would like improved studentsâ vocabulary used scrabble. According to the research could be knows that the studentsâ average score improved from first cycle to the second cycle. According to the last test knows that the average score in the first cycle was 64.63. While, in the second cycle become 77.34. Based on the result, the researcher concluded that teaching vocabulary used scrabble could be improved studentsâ vocabulary at sixth grade students of SD Negeri 007 Bangun Purba